Period of Creative Behavior for personin in Achieving Entrepreneurial for The new Organaization - محمد علي, عالية جواد (Journal of Economics and Administrative Sciences, 2016)
Experienced organizations in recent years, significant challenges , especially with the spread of economic globalization, making it required to provide new and better through experience , creativity and innovation to achieve the quality and high-quality products of all kinds , in order to achieve the objectives of the study and to answer its questions tested the study in the woolen Industries sector in Baghdad . The study was applied to a sample of 30 people in the senior management and the middle and lower in the company (managers of sections  , and  managers of people , and managers of the units , and office managers ) and for the processing of data and information used several statistical methods and extracted results using software (SPSS), where the study found to a set of Conclusions wich hold of the mane variables (Creative Behavior and entrepreneurial organizations ) In the company researched and the existence of relationships significant correlation with each other, as well as having a significant effect of the variable behavior creative in achieving the leadership of the company, and these results were contrary to the hypotheses developed for the study, and the study was presented a set of proposals notably the continuation of the departments attention creators and adopt their ideas and suggestions and develop their abilities in the company to achieve leadership and excellence among local and international companies to compete with other proposals are important for the departments of companies that aim to achieve a leading position in its field.